2021
DOI: 10.21037/jtd-21-755
|View full text |Cite|
|
Sign up to set email alerts
|

The association between the ERCC1/2 polymorphisms and radiotherapy efficacy in 87 patients with non-small cell lung cancer

Abstract: Background: This study sought to investigate the association between the ERCC1/2 single-nucleotide polymorphisms (SNPs) and the efficacy of radiotherapy and prognosis in patients with non-small cell lung cancer (NSCLC). Methods: We examined 6 SNPs in the ERCC1 and ERCC2 genes in 87 consecutive patients with NSCLC who were treated with definitive radiotherapy. The objective remission rates (ORR), overall survival (OS), and progressive-free survival (PFS) were assessed. A Cox regression analysis was conducted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Within this frame, the identification of biomarkers that can predict radiation sensitivity and/ or clinical outcomes will enable NPC patients to benefit from a personalized therapy. Many studies in the last few decades have reported that SNPs in DNA repair genes could be correlated with radiotherapy response in a variety of cancers, including non-small cell lung cancer (NSCLC) (Jiang et al, 2021), rectal cancer (Qin et al, 2015), breast cancer (Lee et al, 2020), head and neck squamous cell carcinoma (HNSCC) (Jin et al, 2014) and NPC (Borchiellini et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this frame, the identification of biomarkers that can predict radiation sensitivity and/ or clinical outcomes will enable NPC patients to benefit from a personalized therapy. Many studies in the last few decades have reported that SNPs in DNA repair genes could be correlated with radiotherapy response in a variety of cancers, including non-small cell lung cancer (NSCLC) (Jiang et al, 2021), rectal cancer (Qin et al, 2015), breast cancer (Lee et al, 2020), head and neck squamous cell carcinoma (HNSCC) (Jin et al, 2014) and NPC (Borchiellini et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, the association between ERCC1 C118T SNP and chemoand/or radio-therapy outcome is well documented and discussed in different cancers. In this field, Jiang et al have shown that this SNP can play an important role in the prediction of radiotherapy sensitivity and prognosis of NSCLC (Jiang et al, 2021). Indeed, NSCLC patients carrying the C allele (CC or CT genotypes) had a significantly better survival compared to those bearing the T allele (TT genotype) (30.9 vs. 16.2 months; P=0.003).…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that mutations in the PIK3CA gene, coding for the catalytic subunit p110 of the phosphatidylinositol 3′-kinase (Pl3K), are related to cell radiosensitivity. On the other hand, a relationship between RT efficacy and genetic polymorphism in the DNA repair genes ERCC1/2 has been demonstrated in patients affected by NSCLC [ 57 , 58 ]. Gong et al [ 59 ] demonstrated the association between RT efficacy and rs 25487 polymorphism in the DNA repair gene XRCC1 in patients affected by esophageal cancer.…”
Section: Molecular and Cellular Features Associated With Radioresistancementioning
confidence: 99%